Previous binaural experience supports compensatory strategies in hearing-impaired children's auditory horizontal localization. - Andrea Gulli; Federico Fontana; Alessandro Aruffo; Eva Orzan; Enrico Muzzi (PLoS ONE)
This study investigates auditory localization in children with a diagnosis of hearing impairment rehabilitated with bilateral cochlear implants or hearing aids. Localization accuracy in the anterior horizontal field and its distribution along the angular position of the source were analyzed. Participants performed a localization task in a virtual environment where they could move their heads freely and were asked to point to an invisible sound source. The source was rendered using a loudspeaker set arranged as a semi-circular array in the horizontal plane. The participants' head positions were tracked while their hands pointed to the auditory target; the preferred listening position and the onset of active strategies involving head movement were extracted. A significant correlation was found between age and localization accuracy and age and head movement in children with bilateral hearing aids. Investigating conditions where no, one, or both hearing devices were turned off, it was found that asymmetrical hearing caused the largest errors. Under this specific condition, head movement was used erratically by children with bilateral cochlear implants who focused on postures maximizing sound intensity at the more sensitive ear. Conversely, those with a consolidated binaural hearing experience could use dynamic cues even if one hearing aid was turned off. This finding may have implications for the clinical evaluation and rehabilitation of individuals with hearing impairments.